Temporal projection of an input-output tables series for the region of Asturias - Carmen Ramos Carvajal; Esteban Fernández Vázquez (European Regional Science Association (ERSA), 2002)
The interest on regional economics has strongly developed in the lastest decades; however, and in spite of the great extension of the information that statistical sources of data offer to economic researchers, one of the major problems arising with these kind of studies still keep being the lack of data. Regional studies can be focused from several points of view, one of these is the input-output framework. This method allows the economic researcher to analyze the intersectorial relationship underlying on a economy in a joint way, as well as the aggregate demand, so it makes feasible to get a integrated knowledge of economic activity. This technique is a key part on the konwledge of a region, because supplies the necesary information to study the economic situation of the mentioned region. However, its use now at days is quite restricted because the discontinuity in the publications of the input-output (IO) tables by statistical agencies, as well as the long time is necessary to wait between each published table. Specifically, focusing the problem on the region of Asturias (north of Spain), the last available input-output table was made for 1995, having been published in 1999. Having account this situation, we believe that for an effective and rigorous application of this kind of analysis a previous step we must take is the input-output tables series estimation. The input-output table elaboration is a work that implies a great effort to get statistical information, as well as a very high cost on every kind of resources. So, the IO tables obtaining by the use of indirect (semidirect) methods of estimation would reduce the needs for information and material and human resources. The information theory is being applied in the latest decades as a very flexible tool that allows to estimate the IO tables coeficients when the available data are not perfectly consistent. Our aim in this work is to make a comparison between the cross entropy method, an information theory derivated thecnique, and the biproportional RAS method, with a long tradition on applied works (Robinson et al. 1998, Mc Dougall, 1999). On a second stage, and basing on the conclusions for the previous comparison and our information availabilities, we will estimate the the input-output tables series corresponding to the region of Asturias for the years 1995-2000. For this estimation, we will apply a cross-time analysis taking as starting point the IOT for Asturias in 1995.
Keywords: 330